STUDI POTENSI PEMANFAATAN NILAI EKONOMI SAMPAH ANORGANIK MELALUI KONSEP DAUR ULANG DALAM RANGKA OPTIMALISASI PENGELOLAAN SAMPAH (Studi Kasus : Kota Magelang) - Winardi Dwi Nugraha; Denok Ambun Suri; Syafrudin Syafrudin (TEKNIK, 2007)
Waste composition of Magelang City in the year of 2006 consists of 69, 65% organic waste and inorganicwaste 30, 35%. This composition indicates that Magelang City have potency to lessen its waste by applying3R concept and by optimizing the role of trash collector in managing inorganic waste. The existing wastemanagement condition shows that organic and inorganic wastes are not separated yet from its source. As aresult, inorganic waste (which is still economically valuable and still can be recycled) was brought to TPS.The target of this research is to find the waste amount and potency that can be recycled. These resultcontinued by planning the operational technique with 3R concept in Magelang City Waste Management.The research method in measuring volume and composition of waste is according to SNI 19-3964-1994.The result shows in year 2007, the quantity of inorganic waste that economically valuable beforeoptimalization is 1880,625 kg/day (4 %) and after optimalization is 6245,28 kg/day (13,28 %). While theincome of trash collector increase from Rp. 2.424.871,00 per day to Rp 8.052.679,00 per day. By applyingthis concep,t the waste managed by trash collector will increase495,67% from17,77 m3/day become 105,87m3/day in the year of 2023. Beside, by applying this 3R concept Magelang City can reduce the wasteoperational cost equal to 14, 27%.